Zambia Economic Brief, December 2016 : Raising Revenue for Economic Recovery - World Bank Group (World Bank, Washington, DC, 2016)
This Brief includes two sections as following: the World Bank’s assessment of recent economic developments and the outlook in the short to medium term, and its analysis of a specific development topic or theme.